Analysis of the chemical components of the essential oil fraction of betel leaf (piper bettle linn.) and the antibacterial activity test against several types of gram-positive bacteria - Alec Baldwin (Institute of Accounting Research and Novation (IARN), 2022)
Beetle (Piper betle Linn) is a plant belonging to the Piperaceae that is often used in beetle chewing. Essential oil fractions of beetle leaves were given by steam and water distillation and fractionated based on time periods. The results showed that the fractional yields of F1, F2, F3 and F4 were 0.061%, 0.034%, 0.027% and 0.015%. respectively. Analysis of essential oils by GC-MS showed that 5 main chemical components were chavibetol, caryophyllene, patchouli alcohol, phenol,2-methoxy-4(1-prophenyl)-acetate and 4-allyl-1,2-diacetoxybenzene respectively. All of these main chemical constituents were proposed to be responsible for its antibacterial activity. The anti-bacterial activity of essential oils of beetle leaves was evaluated with a microdiluton method. The results showed all of essential oil fractions tested active against Staphylococcus epidermidis and Steptococcus mutant but not active to Bacillus subtilis. The MIC values ​​of Staphylococcus epidermidis for all of essential oil fractions were 0.25%, while Steptococcus mutant was the most sensitive to fourth fraction by 0.25%. Inhibition mechanism their activity was indicated through microbial cell walls vandalism test after treatment 1 MIC and 2 MIC of the oils.